2000
DOI: 10.1093/jnen/59.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Neurotrophin Receptor p75NTRin Medulloblastomas Is Correlated with Distinct Histological and Clinical Features: Evidence for a Medulloblastoma Subtype Derived from the External Granule Cell Layer

Abstract: Abstract. Medulloblastomas (MBs) are primitive neuroectodermal tumors (PNET) of the cerebellum. They represent the most frequent malignant pediatric brain tumors, but their origin still remains unresolved and controversial. MB cells correspond to different stages of neural development and differentiation as illustrated by their expression of neuronal and glial markers. In the present study, we examined the expression pattern of the common low-affinity neurotrophin receptor p75 NTR in a series of 167 MBs by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
6

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 44 publications
7
47
0
6
Order By: Relevance
“…Histologically, MBEN contains large nodules with low proliferative activity and advanced neurocytic differentiation, as well as smaller areas with proliferative cells that are embedded in a dense reticulum fiber network. The latter areas resemble the more frequent DMBs, which are believed to arise from granule cell progenitors of the cerebellum and that frequently carry activating mutations of genes encoding for components of the Hedgehog-Patched signaling pathway (14,37). Similar to a previous study (8), our study confirms in greater detail that desmoplastic variants are associated to better prognosis in infants.…”
Section: Discussionsupporting
confidence: 87%
“…Histologically, MBEN contains large nodules with low proliferative activity and advanced neurocytic differentiation, as well as smaller areas with proliferative cells that are embedded in a dense reticulum fiber network. The latter areas resemble the more frequent DMBs, which are believed to arise from granule cell progenitors of the cerebellum and that frequently carry activating mutations of genes encoding for components of the Hedgehog-Patched signaling pathway (14,37). Similar to a previous study (8), our study confirms in greater detail that desmoplastic variants are associated to better prognosis in infants.…”
Section: Discussionsupporting
confidence: 87%
“…The same has been postulated for human medulloblastomas, particularly those with a desmoplastic appearance (Buhren et al, 2000;Kadin et al, 1970;Miyata et al, 1998). Desmoplastic tumors -which represent 20-30% of human medulloblastomasfrequently harbor mutations in the Shh pathway, and have a gene expression profile that resembles normal GCPs (Pomeroy et al, 2002).…”
Section: Pre-neoplastic Cells Arise From Proliferating Granule Cell Pmentioning
confidence: 73%
“…Previous studies have suggested that medulloblastoma arises from granule cell precursors (Buhren et al, 2000;Kadin et al, 1970;Miyata et al, 1998). To determine whether preneoplastic cells express markers of the granule cell lineage, we crossed patched +/-mice with Math1-GFP mice (Lumpkin et al, 2003).…”
Section: Pre-neoplastic Cells Express Markers Of Immature Granule Cellsmentioning
confidence: 99%
“…MB is also found in approximately 20% of offspring from heterozygous transgenic mice carrying a targeted deletion of the Ptch gene that results in constitutive Hh signaling (Goodrich et al, 1997;Wetmore et al, 2001). Both Wnt and Hh signaling pathways play crucial roles in the proliferation and differentiation of cerebellar granule cells, from which MBs are thought to arise (Yokota et al, 1996;Buhren et al, 2000).…”
Section: Introductionmentioning
confidence: 99%